EVALUASI SHELTER SEBAGAI TEMPAT EVAKUASI SEMENTARA (TES) DI KOTA PADANG - yolania alifah; Endah Purwaningsih (JURUSAN GEOGRAFI FIS UNP, 2020)
This research aims: 1) Determine the capacity, radius and facilities in each shelter in Padang city. 2) Knowing the role and level of public concern in maintaining shelters in Padang city. This type of research is a combination research (mixed methods). The type of data used in this study are primary and secondary data with data analysis techniques are the Service Area Analyst in the network analyst extension and Snowball Sampling. The results of this study are: 1) Nurul Haq shelter can accommodate 2,946 people, Darussalam shelter can accommodate 1,683 people and Ulak Karang shelter can accommodate 768 people. 2) The range of services at Darussalam shelters included in the Low category, Nurul Haq shelter in the Medium category and Ulak Karang shelter in the Medium category. 3) Inadequate facilities at the shelter. 4) The level of public knowledge of shelters still needs to be increased in case with the role of the government and related parties. 5) The incomplete facilities available at the shelter affect the trust and utilization of the community towards the shelter. 6) Community roles and concerns are still lacking in shelters.